Third time is the charm? Adoption and recontextualisation of the German dual model in Mexico - Víctor Aramburu Cano; Hugo Javier Fuentes Castro; José Antonio Cervantes-Gómez (Cogent Education)
This article examines the adoption and recontextualisation of the German dual apprenticeship model into the Mexican dual apprenticeship model (MMFD in Spanish) through a cultural political economy approach to policy analysis. We analysed the interests, discourse drivers, and resources of involved and absent actors as explanatory variables for MMFD’s institutional configuration. Key actors included federal education agencies, business chambers, and the German International Cooperation Agency, while the Ministry of Labour, the Ministry of the Economy, and trade unions were notably absent. Consequently, MMFD reflects the interests of the governing clique and organised business—both national and international—while excluding the organised working class. The MMFD also framed youth unemployment as a consequence of skills mismatch, overlooking Mexico’s slow-growth economy under neoliberalism since the 1980s. Our qualitative case study reconstructed the policy transfer process using official documents, statistics, and 40 semi-structured interviews analysed within the cultural political economy framework. Triangulating data sources allowed us to reconfirm our findings. Mexico’s adoption of MMFD is a reference for developing countries to extract lessons for policy transfer and adoption.